Six1 and Six2 of the Sine Oculis Homeobox Subfamily are Not Functionally Interchangeable in Mouse Nephron Formation - Xu, Jinshu; Li, Jun; Ramakrishnan, Aarthi; Yan, Hanen; Shen, Li; Xu, Pin-Xian (Frontiers in Cell and Developmental Biology, 2022)
The vertebrate Six1 and Six2 arose by gene duplication from the Drosophila sine oculis and have since diverged in their developmental expression patterns. Both genes are expressed in nephron progenitors of human fetal kidneys, and mutations in SIX1 or SIX2 cause branchio-oto-renal syndrome or renal hypodysplasia respectively. Since ~80% of SIX1 target sites are shared by SIX2, it is speculated that SIX1 and SIX2 may be functionally interchangeable by targeting common downstream genes. In contrast, in mouse kidneys, Six1 expression in the metanephric mesenchyme lineage overlaps with Six2 only transiently, while Six2 expression is maintained in the nephron progenitors throughout development. This non-overlapping expression between Six1 and Six2 in mouse nephron progenitors promoted us to examine if Six1 can replace Six2. Surprisingly, forced expression of Six1 failed to rescue Six2-deficient kidney phenotype. We found that Six1 mediated Eya1 nuclear translocation and inhibited premature epithelialization of the progenitors but failed to rescue the proliferation defects and cell death caused by Six2-knockout. Genome-wide binding analyses showed that Six1 selectively occupied a small subset of Six2 target sites, but many Six2-bound loci crucial to the renewal and differentiation of nephron progenitors lacked Six1 occupancy. Altogether, these data indicate that Six1 cannot substitute Six2 to drive nephrogenesis in mouse kidneys, thus demonstrating that the difference in physiological roles of Six1 and Six2 in kidney development stems from both transcriptional regulations of the genes and divergent biochemical properties of the proteins.